Dampak Sosial Bentuk Ganti Rugi Pengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum Terhadap Keberlanjutan Hidup Masyarakat - Arya Permana Salaka; Rofi Wahanisa (Universitas Muhammadiyah Kotabumi, 2026)
This study aims to analyze the detrimental social impacts arising from non-comprehensive compensation determination in land acquisition for public interest development on affected communities, and to identify social variables influencing the livelihood sustainability of affected communities following land acquisition. Furthermore, this study seeks to reconstruct a sustainable land acquisition compensation system by considering social impacts and livelihood sustainability of affected communities, particularly farmers who previously depended on their land as their primary income source. This research employs a doctrinal normative legal approach, utilizing library research to collect and analyze legal sources in formulating solutions to the issues examined. The findings indicate that compensation must not be limited to monetary forms, but must also encompass resettlement, provision of replacement land for farmers, and preservation of community structures to prevent social disintegration. The current compensation system contains legal gaps in its implementation and has a strong tendency to produce detrimental social impacts on affected communities, particularly regarding livelihood sustainability following land acquisition.